O uso do P300 como ferramenta para avaliação do processamento cognitivo em envelhecimento saudável - Pavarini, Sofia Cristina Iost; Brigola, Allan Gustavo; Luchesi, Bruna Moretti; Souza, Érica Nestor; Rossetti, Estefani Serafim; Fraga, Francisco José; Guarisco, Letícia Pimenta Costa; Terassi, Marélli; Oliveira, Nathalia Alves; Hortense, Priscilla; Pedroso, Renata Valle [UNESP]; Ottaviani, Ana Carolina (FapUNIFESP (SciELO), 2018)
Changes in patterns of performance for the cognitive functions of memory, processing speed, and focused attention are expected in old age. Objective: The main goal of this systematic review was to analyze the use of ERP in healthy elderly in studies evaluating the P300 components. Methods: A systematic review was carried out based on recommendations for nursing research on the databases LILACS, PsycINFO, PubMed, SCOPUS and Web of Science. Results: 26 studies involving 940 healthy elderly were identified, most of which sought to identify and determine the influence of age on the P300. Conclusion: Although there is consensus in the literature that P300 latency is significantly longer in elderly with psychiatric disorders compared to healthy elderly, it was not possible to conclude P300 associations with gender, education and other cognitive tests.
On the use of the P300 as a tool for cognitive processing assessment in healthy aging a review
Keywords: Aging; Event-related potentials; Healthy elderly; Neuropsychological function; P300